PENYEBARAN SEDIMEN MENGANDUNG MINERAL BERAT DI PANTAI DAN PERAIRAN BAGIAN SELATAN BANYUWANGI - Usman, Ediar (Pusat Survei Geologi, 2007)
Territorial waters of southern part of Banyuwangi are located in the southern slope of Southern Mountains of Jawa, included in fore arc basin which is very rich in heavy minerals. The heavy minerals are the result of volcanic activity along the Southern Mountains of Jawa. Its products have been transported and deposited along the south coast and sea floor of the Southern Waters of Jawa.Results of analysis of sediments collected from the coastal area and sea floor in the southtern part of Banyuwangi, indicate high content of heavy mineral especially magnetite. The heavy minerals which are present within sands are dominated by fine to coarse fractions, i.e. Sand (S), silty sand (zS), sandy silt (sZ) and gravelly sand (gS). They are distributed from coastal plain to offshore area. Some samples show that the content of heavy minerals range from 80 to 100% in weight. Rate of Fe content within magnetite along the sooth part of Banyuwangi ranges between 6,8 and 30, 6%, whereas that on the sea between 3,3- 27,4%. Result of seismic record interpretation shows that thickness of the sediment containing the heavy minerals is approximately 20 meters from sea floor. Keywords: sea floor sediment, heavy mineral, magnetite, southern part of waters, Banyuwangi